2018
DOI: 10.22270/jddt.v8i5-s.1915
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Characterization and Evaluation of Anti-Inflammatory and Anti-Angiogenic Activities of Memecylaene Nanoemulsion

Abstract: The present study was undertaken to formulate and evaluate the anti-inflammatory, anti-oxidant and anti-angiogenic activities of nanoemulsion of Memecylaene.  Memecylaene was isolated from the leaves of Memecylon malabaricum by using various chromatographic methods. An oil-in-water (O/W) nanoemulsion of Memecylaene was formulated by sonication method using sunflower oil (oil phase), Tween 80 (Surfactant) and Ethanol (co-surfactant). The prepared nanoemulsion was characterized for its droplet size, poly dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This observation was consistent with the results of previous studies that demonstrated that exposure to a citrus lemon essential oil nanoemulsion (CLEO-NE) suppressed angiogenesis by decreasing the number and length of blood vessels in the CAM model [77]. In addition, the anti-angiogenic effects of memecylon-NEs on the CAM model were confirmed in a 2018 study that agreed with the present results [78]. The results of a study conducted in 2021 showed that NEs from Artemisia essential oil are able to reduce the number and length of blood vessels and embryonic growth factors, including foetal height and weight.…”
Section: Discussionsupporting
confidence: 93%
“…This observation was consistent with the results of previous studies that demonstrated that exposure to a citrus lemon essential oil nanoemulsion (CLEO-NE) suppressed angiogenesis by decreasing the number and length of blood vessels in the CAM model [77]. In addition, the anti-angiogenic effects of memecylon-NEs on the CAM model were confirmed in a 2018 study that agreed with the present results [78]. The results of a study conducted in 2021 showed that NEs from Artemisia essential oil are able to reduce the number and length of blood vessels and embryonic growth factors, including foetal height and weight.…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, SOD activation was induced by Zn release from MT, since Zn ions are necessary for the formation of the tertiary structure of the SOD molecule, which determines its activity. The foregoing was confirmed by experiments that showed increase of MT antioxidant properties in the presence of zinc [12].…”
Section: Group Of Animalsmentioning
confidence: 61%